Selection of rational parameters of axleboxes with a conic roller bearing (Transport systems and technologies, 2019)
The article discusses the optimization of the design of a two-row conical bearing assembly of a new generation freight wagon. Optimization methods, the choice of a computational model and parameterization criteria are discussed. In the ANSYS software package, computer simulation of the stress-strain state of a tapered bearing assembly has been performed. Based on the calculation results, the stress distribution in the tapered bearing was obtained and bottlenecks in the design of a typical adapter were found and the main possible directions for optimizing the model under consideration were identified.The results are obtained using the ANSYS software package, which consists of a finite element method analysis module and an optimization module based on a sequential quadratic approximation algorithm. The versatility of the complex is that it allows the use of various ITU programs as an analysis module.Requirement means that when looking at food, there is a basic respect for the design and technology of the products themselves. Nourishment of optimized construction of the bookcase for the care of the evenly divided number of navigational attitudes lacked respect. The study made it possible to analyze the stress-strain state of the bearing assembly. Recommendations for optimization of the construction of the semi-axle have been developed.
Keywords: optimization, half-axlebox, roller, bearing, stress, modeling